Преобразуйте в многочлен . (25 )
(y+2)^2+2y(y+2)
-b(b+5)-(b-6)(b+6)

name64 name64    2   26.01.2020 17:41    0

Ответы
alek09 alek09  27.08.2020 19:56

1)4+9у

2)36-8b

Объяснение:

1)(у+2)×2+2у(у+2)=2у+4+3у+4у=4+9у

2)-b(b+5)-(b-6)×(b+6)=-2b-5b+(-b+6)×(b+6)=-7b-b+36=36-8b

(вроде должно так получиться)

ПОКАЗАТЬ ОТВЕТЫ
cazydays cazydays  27.08.2020 19:56

(y + 2) {}^{2} = ({y}^{2} +4y + 4)

2y(y + 2) = 2y^{2} + 4y

( {y}^{2} + 4y + 4) + (2y {}^{2} + 4y) = 3y {}^{2} + 8y + 4

А вот 2 задание сразу ответ:

2b {}^{2} - 5b + 36

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра